Polybenzimidazole adhesive bonded aluminum-2024 joints for structural applications. (December 2019) - Shahzad, Muhammad Faisal; Mughal, M.P.; Iqbal, H.M.S.; Mufti, N.A.; Saleem, M.Q.
Abstract: In the present research, efforts are made to optimize the curing process and bonded joint strength of aluminum 2024 alloy (Al 2024-T3) using polybenzimidazole (PBI) adhesive. Substrate surfaces were prepared using P120 and P1000 sand papers followed by cleaning with ethanol. Substrate surfaces were also prepared using tri-Sodium phosphate (TSP) and the Forest Product Laboratory (FPL) method. Contact angle measurements of untreated surfaces revealed that ethanol cleaned Al 2024-T3 strips exhibited a water contact angle of 86°. A significant decrease in the water contact angle for Al 2024-T3 was noticed with P1000 sanding followed by TSP treatment. The water contact angle of Al 2024-T3 was reduced from 86° to 52° using a combined surface treatment of P1000 sand paper and TSP solution. Lap shear tests were performed to evaluate the single lap shear strength of PBI bonded Al 2024-T3 joints. A maximum lap shear strength of 11.9 MPa was achieved for samples which had received a combined surface treatment of P1000 sand paper and TSP solution. A lap shear strength of 12.1 MPa was achieved using the FPL treatment method. This lap shear strength is almost similar as attained with TSP treated bonded joints. Therefore, the current work also proved TSP as an effective alternative to the hazardous chromate based FPL method for the surface pre-treatment of Al 2024-T3. Fractured surfaces of adhesive bonded joints revealed both adhesive and cohesive failure.